Childhoods and Time: a Collective Exploration - Ribeiro, Camila da Rosa (2023)
This collective piece explores the philosophical, ontological, and epistemic potentials of analyzing the relations between childhood and time, proposing thought experiments and fieldwork analyses that release childhood from a linear temporality toward (modern) adulthood. Each experiment originating from the authors' distinct scholarly positionings fractures modern childhood and its civilization project, built from the hegemony of linear, sequential, progressive, and principled time.